Psychopathology and resilience in relation to abuse in childhood among youth first referred to the psychiatrist - Pejović Milovančević, Milica; Tenjović, Lazar; Išpanović, Veronika; Mitković, Marija; Radosavljev Kirćanski, Jelena; Minčić, Teodora; Miletić, Vladimir; Draganić Gajić, Saveta; Lečić Toševski, Dušica (Vojnosanitetski pregled, 2014)
Background/Aim. Child abuse may be related to adverse psychological outcomes in adult life. However, little is known about specific clinical, family and resilience profiles of adolescents that have experienced child abuse. The aim of this study was to investigate clinical symptoms, family functioning and resilience characteristics of adolescents with the experience of abuse, first referred to psychiatrists. Methods. The study included 84 young participants (mean age 14.90 ± 3.10, ranging from 11 to 18 years) as consecutive first referrals to the Clinic for Children and Youth of the Institute of Mental Health, Belgrade, Serbia. The sample consisted of two groups, based on the Child Abuse Matrices of Risks. The first group included adolescents with the experience of abuse in childhood (n = 38, 13 males, 25 females), whereas the second, control group, comprised of non-abused adolescents (n = 47, 20 males, 27 females). The presence of abuse was evaluated by the Child Abuse Matrices of Risks. The study used the following questionnaires: Youth Self-Report (YSR), Adolescent Resilience Attitudes Scale (ARAS), and Self-Report Family Inventory (SFI). Results. Significant differences were found only among females. According to YSR, the abused girls had significantly higher scores on the Delinquent Behavior scale and marginally higher scores on Anxious/Depressed and Social Problems scales. Analyses of the SFI showed significantly lower family functioning among the girls with the child abuse history for all scales except for the Directive Leadership. The abused girls also showed significantly lower scores on the Insight scale, and marginally lower Initiative scores at the ARAS. Conclusions. These findings may have practical application in the creation of specific preventive and treatment strategies, particularly focused on delinquent tendencies, as well as on enhancing resilience through providing positive environments within families, schools and communities.
Keywords: psychopathology; resilience; psychological; child abuse; adolescent psyhiatry